2017
DOI: 10.1161/hypertensionaha.116.08547
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Placental Growth Factor in Women With Suspected Preeclampsia Attending Antenatal Facilities in Maputo, Mozambique

Abstract: C omplicating an estimated 3% to 10% of pregnancies, the hypertensive disorders of pregnancy account for an estimated 46,000 maternal and 500,000 perinatal deaths annually, with >99% of these deaths occurring in less-developed countries, including Mozambique.1,2 The most dangerous of the hypertensive disorders of pregnancy is preeclampsia, the origins of which lie in a mixture of maternal and placental factors.3,4 Currently, delivery is the only mechanism by which to initiate the resolution of preeclampsia, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…The low rate of use of antenatal corticosteroids (0•7%) in this cohort of women is consistent with the findings in our previous Maputo-based study (8) We have identified that introducing PlGF into clinical care in antenatal clinics is associated with increased identification of women who are deemed to require transfer to higher levels of care.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The low rate of use of antenatal corticosteroids (0•7%) in this cohort of women is consistent with the findings in our previous Maputo-based study (8) We have identified that introducing PlGF into clinical care in antenatal clinics is associated with increased identification of women who are deemed to require transfer to higher levels of care.…”
Section: Discussionsupporting
confidence: 90%
“…In this implementation study, we have determined that among women with preeclampsia who attended prenatal clinics in Maputo, Mozambique, the introduction of a package of care, including the use of PlGF, was associated with both an increased detection of preeclampsia and an increased number of transfers of care. In addition, low maternal plasma PlGF identified women destined to deliver soon and have more complicated pregnancies, as determined previously using masked PlGF results (8). Also, we have determined that maternal plasma PlGF <40 -50 pg/ml identifies a group of women at exceptionally high risk for suffering an intrauterine fetal death (32•6% of women with PlGF <50 pg/ml).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A wide external validation in other populations would be desirable. Currently, substantial data are being generated worldwide, including in low‐income countries, which will hopefully help to address this matter …”
Section: Prediction Of Diseasementioning
confidence: 99%
“…Ukah et al in a prospective cohort study of pregnant women attending antenatal care in Maputo, Mozambique, measured the serum PlGF concentration in women suspected of having preeclampsia after 20 weeks of gestation. This study had as its primary outcome, the time-to-delivery after confirmation of preeclampsia [36]. This study differed from ours in terms of being a diagnostic study rather than a prediction study.…”
Section: Discussionmentioning
confidence: 86%